Código deontológico y su aplicación en los medios impresos de la Provincia de Los Ríos - Gáleas Gaibor, Santiago (2020)
This research work is carried out in the province of Los Ríos, specifically in traditional media, in this case, the newspapers El Río, La Hora, El Portavoz, and La Crónica, the research is carried out taking as a starting point the Organic Law of Communication in force in the 2013-2018 period in relation to article 9 that talks about deontological codes and article 10 which describes the parameters that all communication media should have met. The purpose of the case study is to analyze the code of ethics that was in force, (it should be noted that these articles 9 and 10 were repealed and replaced by others). And its application in the provincial print media through the implementation of a descriptive methodology and qualitative approach, using the interview technique to gather information, the same that was directed to the managers and managers of these print media, analyzes of the internal codes mentioned above, where it was possible to determine that some media have not published their own code of ethics and other cases have not issued by themselves.